Identifying the relationship between patient-reported outcomes and treatment with opiates in the adult emergency department – A cross-sectional study. (May 2022) - Althagafi, Suhair M; Hughes, James A
Highlights: The APS-POQ-R allows clinicians to identify the patient-reported outcomes of pain care in the ED. The receipt of opiate medications does not alter the overall patient-reported outcomes of pain care in the ED. Patients who receive an opiate perceive better pain care but report no difference in other areas.